Analisis Faktor Lingkungan Dan Kondisi Individu Yang Berhubungan Dengan Kelelahan Fisik Pada Pekerja Pandai Besi Di Kecamatan Tikala, Kabupaten Toraja Utara: Pendekatan Cross-Sectional - Ruhban, Andi; Arif, Muhammad Ikbal; Haderiah, Haderiah; Lidung, Harvino Hesty (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Blacksmithing is part of the informal sector that continues to thrive amidst modern industrial development, especially in culturally rich regions such as Tikala District, North Toraja Regency. This sector not only supports the local economy but also represents a vital aspect of cultural identity. However, blacksmithing requires intense physical effort, which may lead to physical fatigue among workers. The aim of this study was to identify the factors associated with physical fatigue among blacksmith workers in Tikala District. This research employed a quantitative design with a cross-sectional approach. A total of 78 respondents were selected using random sampling from 12 blacksmithing sites. Data were collected through interviews using a questionnaire, as well as direct measurements of workplace temperature, age, work duration, and pre-existing medical conditions. Data analysis was conducted using the Chi-Square test to determine the relationship between independent variables and physical fatigue. Univariate analysis showed that 21 respondents (26.9%) experienced physical fatigue. The Chi-Square test results indicated a significant relationship between physical fatigue and environmental temperature (p=0.007), age (p=0.009), work duration (p=0.039), and pre-existing medical conditions (p=0.004). These factors contributed to the increased risk of physical fatigue among blacksmith workers. In conclusion, there is a significant relationship between temperature, age, work duration, and pre-existing medical conditions and the occurrence of physical fatigue among blacksmith workers in Tikala District, North Toraja Regency. Therefore, it is recommended for future researchers to explore other variables such as workload, nutritional status, rest duration, or ergonomic factors to gain a more comprehensive understanding of physical fatigue. Keywords: Physical Fatigue, Age, Temperature, Work Duration, Pre-existing Medical Condition